Students’ learning styles preferences and the teachers’ awareness on their students’ learning preferences / Nor Azurainie Adnan - Adnan, Nor Azurainie (2011)
This study focus on the learning styles preferences among the learners and teachers’ awareness on their students’ preferences learning styles in English language. The sample for this study involved the upper secondary students and also the teachers who are teaching them for the English subject. A set of questionnaire consists of two version ( teachers and students version ) had been distributed to collect the data from the students’ and teachers’ views on the items related. The findings showed that there are some areas that the teachers and the students holds the same views and agreements on the English language learning preferences and there are also some areas that both the teachers and students have a mismatch views on the language learning preferences. This study also revealed that there are some areas that the teachers aware and are not aware on their students preferences on the English language learning. Thus, the less elements and focus that has been undermine in language teaching and learning process should be given priority and consideration in order to fulfill the students’ needs for their learning process. The outcomes of this study would benefit most the teachers and students who are involved in this study. In addition, other organizations and related groups could also benefit from this study for the future planning and implementation of the activities and curriculum in the teaching and learning process for English language.